Menggali Makna Keluarga: Pendidikan Agama Kristen sebagai Instrumen Perubahan Perilaku Anak yang Signifikan - Subaedah Luma (Harati: Jurnal Pendidikan Kristen, 2024)
This article discusses the central role of Christian Religious Education (CRE) in shaping the character and behavior of children, especially within the family context. The research highlights the family as an entity formed based on the will of God, emphasizing the significant impact of CRE within the family on the moral development, values, and life perspectives of children. The research methodology utilized for this study involves literature analysis to delve into the role of CRE within the family. The article underscores the vital role of parents as educators, creating Christian values that can be internalized. Additionally, the article addresses challenges while providing existing solutions. Thus, this article presents the crucial contribution of CRE in shaping the moral and ethical foundations of children within the family context, emphasizing the pivotal role of the family as the primary agent in the process of socialization and Christian religious education.